How do different perceived school goal structures affect Chinese kindergarten teachers’ professional identity? The role of basic psychological needs satisfaction and growth mindset - Wei Luo; Xingcan Ni; Chundie Wang; Jiaqin Wang; Yujia Zeng; Chengfu Yu (Frontiers in Psychology)
IntroductionDue to the unique challenges and high-intensity emotional labor in their work, kindergarten teachers’ high levels of job burnout and turnover rate have become a widely recognized social issue. To address this situation, exploring the key factors that enhance kindergarten teachers’ professional identity is of paramount importance. Professional identity development is influenced not only by the cultural contexts and workplace environment but also by individual teacher characteristics. However, existing research on how environmental and psychological factors interact to influence the professional identity of kindergarten teachers is scarce.MethodsThis study examined the effects of perceived school goal structure on kindergarten teachers’ professional identity and explored the mediating role of basic psychological needs satisfaction (BPNS) and the moderating role of growth mindsets. A questionnaire survey was conducted with 1,475 kindergarten teachers from China, selected using random sampling.ResultsThe results demonstrated that school learning and performance goal structures indirectly affected teachers’ professional identity through the mediating role of BPNS; however, only the school learning goal structure directly affected professional identity. Additionally, growth mindsets only moderated the relationship between school performance goal structure and BPNS. Regardless of the school performance goal structure, teachers with strong growth mindsets reported higher levels of BPNS than those with weak growth mindsets.DiscussionThis study provides a solid theoretical foundation and practical guidance for improving teachers’ professional identity within the unique sociocultural context of China.